(untitled) (Bioscience Journal, 2019)
Yacon is a functional food with great potential for horticultural exploitation and its cultivation demands the generation of agronomic information. To address these needs, this study was performed to evaluate the production of yacon planted in different planting seasons under two growing conditions in Brazil. The experiments were conducted in two different locations, one in the mountain region (tropical microclimate at altitude with milder temperatures) and the other in the lowland region (warm tropical microclimate with higher temperatures). At both sites, yacon was planted in four seasons: autumn (April), winter (July), spring (September) and summer (December). At harvest, the tuberous roots were evaluated for leaf area index and the variables of vegetative development and productivity of plants (for total and standard commercial roots). It was concluded that yacon cultivation in mountain conditions (tropical climate with milder temperature) promotes the development and production of yacon. Additionally, planting in the autumn for both growing conditions (mountain or lowland) promotes the development and production of yacon, including increased production of roots of better commercial grade, allowing greater economic profitability. These results indicate that temperature has an influence on the growth and yield of the tuberous roots of yacon, and milder temperatures were more favourable.